Prevalence of chronic kidney disease in Saudi Arabia: an epidemiological population-based study - Mohammed A. Alshehri; Husain Y. Alkhlady; Zuhier A. Awan; Mohammed Ridha Algethami; Hadiah B. Al Mahdi; Hussam Daghistani; Khalid Orayj (BMC Nephrology)
Abstract Background Chronic kidney disease (CKD) is a prevalent global health issue affecting millions of patients worldwide, impacting quality of life, impeding physical and psychological well-being, causing financial stress, and increasing mortality rates. This study aimed to highlight the prevalence of CKD and its associated risk factors across Saudi Arabia. Method: This is a cross-sectional study conducted from 2015 to 2022, using data from 42 branches of a major network of diagnostic laboratories in Saudi Arabia, covering the country's 13 administrative areas. Results The mean age was 40.35 ± 14.5 years. The highest proportion of participants resided in the Makkah region at 35.77%, followed by the Riyadh region at 25.75%. The overall prevalence of CKD was 4.76%, with most having CKD in stage 3 (3.5%). The prevalence of CKD was higher among males compared to females (5.83% vs. 3.88%) and increased significantly with age, being 0.45% among participants aged 18–29 years and reaching 50.94% among participants aged 90 years or older. Predictors of CKD included increasing age, male sex, administrative area (Makkah 1.40 [95% CI:1.26–1.55], Jazan 1.34 [95% CI:1.18–1.52], Najran 0.47 [95% CI, 0.39–0.57], Alqasim 0.73 [95% CI, 0.64–0.82]), and a high hemoglobin A1C. CKD in Saudi Arabia is influenced by various demographic and geographic determinants contributing to its prevalence and associated burden on the population. Conclusion These findings emphasize the need for targeted screening and prevention strategies, especially for at-risk populations. Continued surveillance, early detection, and effective management are crucial to reducing CKD's burden and improving kidney health outcomes in Saudi Arabia. Further research is essential to better understand the disease's regional and demographic drivers.